Bioactive Compounds From Marrubium vulgare L. based on in vitro antioxidant Activity - Shamil Ismail Neamah; Ismail Ahmed Sarhan; Oqba NAFIA Al-Shay (Journal of Global Pharma Technology, 2018)
Marrubium vulgare L. (Lamiaceae) used in the world a viable source of medically important. Six compounds included: flavonoids, triterpenoids, and phenolic acid, they were isolated from the leaf extract by methanolic solvent and were determined as luteolin-7-O-β-glucopyranoside (1), apigenin-7-O-β-glucopyranoside (2), oleanolic acid (3), β-sitosterol (4) luteolin-7-O-rutinoside (5), and rosmarinic acid (6). In the MTT assay, compounds 1-6 at 250 µg/mL concentration gave an absorbance value of 0.524, 0.455, 0.187, 0.088, 0.0362, and 0.241, respectively. The significant LPO inhibitory of the purifications afforded compounds 1, 2, and 5 by 66, 84, and 89 at 100 µg/mL concentration, respectively.